DNA methylation of the 5′‐UTR DAT 1 gene in Parkinson's disease patients. (3rd June 2020) - Rubino, Alfonso; D'Addario, Claudio; Di Bartolomeo, Martina; Michele Salamone, Enrico; Locuratolo, Nicoletta; Fattapposta, Francesco; Vanacore, Nicola; Pascale, Esterina
Abstract : Objectives: The involvement of epigenetics mechanisms in the transcriptional regulation of key genes has been investigated in the initiation and progression of neurodegenerative disorders, including Parkinson's disease (PD). Among others, we, here, focused the attention on the dopamine transporter (DAT) gene playing a critical role in maintaining the integrity of dopaminergic neurons. Materials and Methods: We performed bisulfite pyrosequencing to examine DNA methylation levels of six CpG sites in the 5′‐UTR of DAT1 gene in human peripheral blood mononuclear cells (PBMCs) obtained from 101 sporadic PD patients and 59 healthy controls. Results: We selectively report for CpG5 an increase in DNA methylation levels in PD subjects respect to controls, that almost reaches statistical significance (30.06 ± 12.4 vs 26.58 ± 7.6, P = .052). Of interest, a significantly higher methylation at specific CpG sites (ANOVA: P = .029) was observed in PD subjects with advanced stage of illness. Namely, a multivariate regression analysis showed that a higher methylation level at specific CpG sites in the group of PD patients was associated with increased methylation at CpG2, CpG3, and with H&Y stage but not with age and gender. This regression model explains the 38% of the variance of methylation at CpG5. Conclusion: Our results do seem to suggest that the methylation level of CpG5 is different between PD patients and controls. Moreover, this methylation level for CpG5 may be associated also with the stage of disease.